Предмет: Математика,
автор: gofd
Покажите подробно как решать этот пример на картинке
Приложения:
Ответы
Автор ответа:
0
(5/ (3-х) - 4х) : (4х^2 - 12x + 5)/ (x - 3)^2 = (x - 3)^2
1) 5/(3 - x) - 4x = 5 - 4x(3 - x) = 5 - 12x + x^2
2) (5 - 12x + x^2) : (4x^2 - 12x + 5)/ (x-3)^2 =
= (5 - 12x + x^2) * (x - 3)^2 : (4x^2 - 12x + 5) = (x - 3)^2
1) 5/(3 - x) - 4x = 5 - 4x(3 - x) = 5 - 12x + x^2
2) (5 - 12x + x^2) : (4x^2 - 12x + 5)/ (x-3)^2 =
= (5 - 12x + x^2) * (x - 3)^2 : (4x^2 - 12x + 5) = (x - 3)^2
Автор ответа:
0
у вас кажется не правильно вышло
Автор ответа:
0
Кляча, ты не правильно решил!
Похожие вопросы
Предмет: Алгебра,
автор: erzatrakhymov
Предмет: История,
автор: Аноним
Предмет: Алгебра,
автор: ravilmetlicki
Предмет: Математика,
автор: sc391114
Предмет: Химия,
автор: Lubsia